Identification and quantification of drugs, metabolites and metabolizing enzymes by LC-MS - Chowdhury, Swapan K.; ScienceDirect eBooks (Amsterdam : Elsevier, 2005)
As new techniques of transferring from liquid to gas phase and measuring masses of drug molecules and metabolites become more prevalent, so do the technical challenges of putting these techniques into proper use, as well as the task of consolidating emerging applications. Identification and Quantification of Drugs, Metabolites and Metabolizing Enzymes by LC-MS, Volume 6 fills the gap in the lack of presently available literature by providing a critical review in the current use of liquid chromatography-mass spectrometry (LC-MS) in drug discovery and development. With chapters written by experts with a wide range of practical experience from the pharmaceutical industry, emphasis is placed on techniques and applications. The book also includes chapters on how to utilize LC-MS instrumentation for current drug metabolism problems. This book is intended for those beginning to use LC-MS for drug metabolism studies as well as for those considered advanced practitioners. * Introduces readers to the practical applications of modern liquid chromatography-mass spectrometry (LC-MS) in a wide range of drug metabolism studies * Provides a comprehensive description of different forms of metabolites, with detailed discussion on the wide range of methodologies used to identify them * Highlights problems associated with drug quantification and offers practical solutions.
Introduction: LC-MS and Drug Metabolism: A Journey Back in Time, Present Trends and Future Direction. -- Strategies for Increasing Throughput for PK Samples in a Drug Discovery Environment. -- Commonly Encountered Analytical Problems and their Solutions in Liquid Chromatography/Tandem Mass Spectrometry (LC/MS/MS) Methods Uded in Drug Development. -- Pitfalls in Quantitative LC-MS/MS: Metabolites Contributing to Measured Drug Concentrations. -- In vitro DMPK Sreening in Drug Discovery, Role of LC-MS/MS. -- Metabolite Identification by LC-MS: Applications in Drug Discovery and Development. -- Screening for the Assessment of Electrophilic Metabolite Formation Early in Drug Discovery Using HPLC-MS. -- Liquid chromatography Tandem Mass Spectrometry-Based Metabolite Identification Strategies in Pharmaceutical Research. -- Quantification and Structural Elucidation of Low Quantities of Radiolabeled Metabolites Using Microplate Scintillation Counting (MSC) Techniques in Conjunction with LC-MS. -- -- Oxidative Metabolites of Drugs and Xenobiotics: LC-MS Methods to Identify and Characterize in Biological Matrices. -- Detection and Charactrization of Highly Polar Metabolites by LC-MS: Proper Selection of LC Column and Use of Stable Isotope Labeled Drug to Study Metabolism of Rabavirin in Rats. -- Cytochrome P450 (CYP) and UDP-Glucuronosyltransferase (UGT) Enzymes: Role in Drug Metabolism, Polymorphism, and Identification of their Involvement in Drug Metabolism.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Drugs -- Metabolism; Enzymes -- Physiology; MEDICAL -- Pharmacology; Chromatography, Liquid -- methods -- electronic information resources [MESH]; Drugs -- Design -- electronic information resources [MESH]; Drugs -- analysis -- electronic information resources [MESH]; Drugs -- metabolism -- electronic information resources [MESH]; Enzymes -- physiology -- electronic information resources [MESH]; Mass spectrometry -- methods -- electronic information resources [MESH]; Drugs -- Metabolism; Electronic books